Case Series: Two Cases of Critical Pulmonary Artery Stenosis Focusing on the Timing of Diagnosis and Management - Koentartiwi, Dyahris; Ramadhanti, Ardhanis; Damayani Susilo, Monica (Fakultas Kedokteran Universitas Brawijaya, 2024)
Critical stenosis of the pulmonary valve in neonates is related to ductus-dependent pulmonary circulation. Percutaneous transcatheter balloon valvuloplasty (PTBV) is the treatment of choice for critical pulmonary stenosis. Unfortunately, many children in developing countries are usually diagnosed late and seldom get immediate care, which leads to delayed growth and development and, ultimately, higher morbidity and mortality. We present two cases of critical pulmonary artery stenosis in a 17-year-old boy and a 4-day-old girl who received PTBV procedures, but had different outcomes. We underline the importance of early diagnosis and intervention in critical pulmonary stenosis for the patient’s prognosis.